A Three‐Dimensionally Interconnected Carbon Nanotube–Conducting Polymer Hydrogel Network for High‐Performance Flexible Battery Electrodes. Issue 12 (22nd April 2014) - Chen, Zheng; To, John W. F.; Wang, Chao; Lu, Zhenda; Liu, Nan; Chortos, Alex; Pan, Lijia; Wei, Fei; Cui, Yi; Bao, Zhenan
<x xml:space="preserve">Abstract</x> High‐performance flexible energy‐storage devices have great potential as power sources for wearable electronics. One major limitation to the realization of these applications is the lack of flexible electrodes with excellent mechanical and electrochemical properties. Currently employed batteries and supercapacitors are mainly based on electrodes that are not flexible enough for these purposes. Here, a three‐dimensionally interconnected hybrid hydrogel system based on carbon nanotube (CNT)‐conductive polymer network architecture is reported for high‐performance flexible lithium ion battery electrodes. Unlike previously reported conducting polymers (e.g., polyaniline, polypyrrole, polythiophene), which are mechanically fragile and incompatible with aqueous solution processing, this interpenetrating network of the CNT‐conducting polymer hydrogel exibits good mechanical properties, high conductivity, and facile ion transport, leading to facile electrode kinetics and high strain tolerance during electrode volume change. A high‐rate capability for TiO2 and high cycling stability for SiNP electrodes are reported. Typically, the flexible TiO2 electrodes achieved a capacity of 76 mAh g–1 in 40 s of charge/discharge and a high areal capacity of 2.2 mAh cm–2 can be obtained for flexible SiNP‐based electrodes at 0.1C rate. This simple yet efficient solution process is promising for the fabrication of a variety of high performance flexible electrodes.